ANALISIS IMPLEMENTASI PROGRAM PEMBINAAN UMKM OLEH INKUBATOR BISNIS DINAS KOPERASI KOTA MAKASSAR DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH - Munawir; Raehana, Syarifa; Bazith, Akhmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are a crucial pillar of the Indonesian economy; however, MSME actors in Makassar City still face numerous challenges, including limited access to capital, low digital literacy, lack of product innovation, and weak marketing strategies. This study aims to analyze the forms of MSME strengthening through the Business Incubator development program of the Makassar City Cooperative Office and to assess its conformity with the principles of Islamic economic law. This research employs a descriptive qualitative approach with data collected through in-depth interviews, observation, and documentation. The results indicate that the incubator program has provided tangible strengthening for MSME actors through business legality facilitation (NIB, PIRT, intellectual property rights), financial management training, product packaging and branding development, and the 10,000 Free Skill Training program. From the perspective of Islamic economic law, this program shows significant conformity with the principles of hifzh al-mal (protection of wealth), economic justice ('adl), prohibition of gharar, and maslahah 'ammah (public benefit). This study recommends a comprehensive strengthening of Islamic values integration within the incubator program to build an MSME ecosystem that excels not only economically but also spiritually.